Technologies in meat traceability, authenticity and safety - Rogberg Muñoz, Andres (2013)
Traceability is an indispensible feature of food safety. It allows providing consumers with information concerning the products but also is crucial for surveillance, i.e. in cases of contamination outbreaks could help into the investigation of the possible and causes. Thus the identification of the origin of food, feed ingredients and food sources is of prime importance, particularly when products are found to be faulty [1]. European regulation EC/178/2002 (applied in 2005) defines traceability as the ability to trace and follow food, feed, and ingredients through all stages of production, processing and distribution [2]. In the U.S., the “Bioterrorism Act” of 2002, authorizes the Food and Drug Administration (FDA) to order the detention of any food, if exists “credible evidence or information” exist to indicating that the article “presents a threat of serious adverse health consequences or death to humans or animals” [3]. Since then a variety of animal identification and traceability systems have been quickly developed and being used for livestock, meat and meat products. Even though, it is still common to notice a confusion in the use of the terms ‘‘identification’’, “traceability” and “verification”. Smith et al. [4] state about the meat industry in US: “it is easy to identify, very difficult to accomplish traceability, and even more difficult to verify identity, traceability and claims about livestock and meat”.